Marketing Buprenorphine for Chronic Pain Management: Overcoming Societal Perceptions and Enhancing Public Health - Perez-Espinosa, Marc; Khanfar, Nile M.; Attarabeen, Omar F.; Pham, Huy; Silva-Suarez, Georgina; Mujtaba, Bahaudin G. (Archives of Business Research, 2025)
As a partial mu-opioid receptor agonist, buprenorphine is safe and effective in lowering the risk of opioid dependency, making it a valuable tool for treating pain. Buprenorphine’s comparative advantages over typical opioids—such as a lower risk of abuse and a good safety profile—are highlighted in the literature review. Despite these advantages, medical and cultural stigma prevents eligible patients from effectively using this medicine. As such, stigma impacts both healthcare providers' views toward prescribing this medication and patients' access to therapy. Using a methodology of thoroughly understanding buprenorphine's potential to redefine therapeutic strategies in public health, this study examines the pharmacological foundations, compare its efficacy and safety with other analgesics, and explore remedies for the stigmas associated with its use This exploratory paper, through literature review of existing data, investigates the multifaceted role of buprenorphine in the management of chronic pain and treating opioid use disorder, emphasizing the challenges posed by stigma and regulatory barriers. This study’s findings lead to a discussion of how academics and marketers may improve public awareness and proper use of buprenorphine by developing educational initiatives. It is recommended that marketers create focused educational initiatives for the public and healthcare professionals with the goal of changing public opinion and raising awareness of buprenorphine as an essential treatment option. It is the responsibility of academics to close research gaps, especially in the areas of understanding and combating stigma via empirical investigations and the use of theoretical frameworks such as the Health Belief Model. The original study advocates for a comprehensive strategy that combines legislative change, activism, and ongoing research to optimize buprenorphine's potential and enhance public health outcomes related to pain treatment and opiate addiction.